Interrogating the Language Gap of Young Bilingual and Bidialectal Students. Issue 1 (2nd January 2017) - García, Ofelia; Otheguy, Ricardo
ABSTRACT: This article describes how the belief in the existence of a language gap has negative educational consequences for bilingual and bidialectal children from minoritized communities. This article first positions the idea of the language gap within the "achievement gap" discourse that has long been prevalent in educational circles. We then identify conceptual problems related to the ways that the language gap has been constructed, problems that we see as undermining its validity. We locate the gap not in the ways families and young children use language but in the ways racism has regimented language so as to exclude language-minoritized children. Insisting on the nature of language as a form of semiosis, we consider how a diverse society can educate its children in ways that extend their meaning-making potential, rather than in ways that restrict it to one autonomous enumerated language in whose reified name only some of the children's structural and lexical features are legitimated. And we end by describing how a theory built around the notion of translanguaging allows us to locate the gap in social, educational, and academic practices rather than in the raciolinguistically minoritized students and their families.